Study of nitrogen behavior during metal processing - Holub , I.V.; Bila , O.V.; Nosko , O.A.; Kovzik , A.M. (Theory and Practice of Metallurgy, 2023)
Goal. Studying the behavior of nitrogen during metal treatment with a gas mixture and during metal deoxidation, because one of the most common methods of steel processing in a ladle is the process of metal deoxidation, blowing of metal with inert gases, and vacuuming of steel. Method. Thermodynamic and kinetic calculations, a mathematical model that allows you to calculate quantitative indicators during deoxidation of metal and during the removal of dissolved gases from metal during out-of-furnace processing and to analyze the processes under investigation. The results. When blowing metal with argon on a ladle-furnace installation, the surface of the metal must be open from slag, but at the same time there is a parallel transition of gas from the atmosphere to the metal, since the slag is a protective coating of the metal from the atmosphere, it has also been proven that the foaming of the slag affects only the nitrogen content in the metal and allows reducing its concentration by 0.001%, it is also proven that nitrogen is not the cause of macrodefects in the metal workpiece. The influence of nitrogen, aluminum, and titanium on the formation of nitrides in a metal previously treated with a gas mixture containing nitrogen was determined. Scientific novelty. Consideration of the thermodynamic and kinetic features of the dissolution of nitrogen in metal during deoxidation, gas blowing of metal into the ladle made it possible to find out the heat and mass transfer processes of the behavior of nitrogen in the metal, which will contribute and possibly lead to the development of a new technology of ladle metal processing. Practical significance. Use a mixture of gases containing nitrogen when blowing a wider range of steels, taking into account the behavior of nitrogen during the deoxidation of metal, which may have an increased content of dissolved nitrogen with the help of sufficient amounts of implanted titanium, it is possible to neutralize the effect of nitrogen in steels containing aluminum, and thereby contribute elimination of defects and improvement of the quality of the cast billet also due to conducting the metal processing process under foamed slag.